Large-scale synthesis of two-dimensional indium telluride films for broadband photodetectors - Zhibin Yang; Jiaxing Guo; Haoran Li; Xiaona Du; Yanan Zhao; Haisheng Chen; Wenwen Chen; Yang Zhang (Materials & Design, 2023)
2D III-VI semiconductors have emerged as promising materials for optoelectronic devices due to their tunable bandgaps, efficient light absorption and high carrier mobility. Among III-VI group, 2D indium telluride (InTe) has been studied very little compared with its well-known congeners such as InSe and GaSe. Although InTe possesses remarkable electrical and optical properties, the investigation of its device applications is greatly hindered due to the shortage of scalable synthesis method. Here, we synthesized centimeter-scale 2D InTe films via a pulsed laser deposition method. The structure of as-grown InTe films was systematically studied, exhibiting good continuity, uniformity and high degree of crystallinity. Meanwhile, layer-dependent bandgaps (1.21∼1.65 eV) were observed from the optical characterization. The InTe based photodetectors show a broadband photoresponse from ultraviolet (370 nm) to near-infrared region (980 nm). The photoresponsivity and detectivity of the InTe photodetectors can achieve 6.35 A/W and 1.55×1011 under 370 nm illumination, respectively, which outperform many photodetectors based on large-area 2D materials. Notably, InTe photodetectors also demonstrate strong layer-dependent photoresponse from 2 L to 10 L upon different wavelength illumination. Our work will inspire the research interests to further develop the practical applications of 2D InTe in the field of photodetection devices.